The Role of Ma'arif Educational Institutions in Providing Learning Facilities and Human Resources in Indramayu Regency - Wiharja, Adis; Nahriyah, Syaf'atun; Syihabuddin , Abu (PT. Anagata Sembagi Education, 2024)
This study aims to describe and analyze the role of the Ma'arif Educational Institution in providing learning facilities and human resource development in Indramayu Regency. The study uses a qualitative approach through field studies and literature with analytical description methods. Data were obtained through observation and interviews with various educational elements. The results show that the provision of adequate facilities and infrastructure has a significant impact on the quality of learning, because the availability of facilities can increase teacher and student motivation. Facility planning is carried out in three stages: annual needs data collection, adjustments to the budget according to priorities, and determination of the final plan. In procuring facilities, the institution uses various methods such as submitting assistance proposals, borrowing, or exchanging goods. Efforts to improve human resources are carried out through guidance, training, and formal and non-formal education that supports employee competence and performance